Peran Literasi Teknologi Informasi dan Komunikasi dalam Pembelajaran Jarak Jauh di Masa Pandemi COVID-19 - Anshori, Fajri; Surojudin, Nurhadi; Suratman, Suratman (Jurnal Pelita Teknologi, 2023)
This article discusses the importance of technological literacy in distance learning during the Covid-19 pandemic. The literature analysis involves four steps, revealing significant adaptations in the education sector. Distance learning requires technology as a link between teachers and learners, but its success depends on adequate technological literacy. This literacy involves understanding from device recognition to information management skills. In the context of distance learning, Technology Literacy and ICT facilitate learning, increase the effectiveness of PES, support communication and collaboration, and encourage the use of technology with socially responsible ethics. The article emphasizes that technology literacy is the key to the success of technology implementation in supporting education in the pandemic era.